1995
DOI: 10.1093/clinids/20.5.1217
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime Monotherapy vs. Ceftriaxone/Tobramycin for Serious Hospital-Acquired Gram-Negative Infections

Abstract: We compared ceftazidime monotherapy with ceftriaxone/tobramycin in a prospective, randomized clinical trial that included 580 patients with serious hospital-acquired infections. One-half of the patients had an underlying disease with a rapidly or ultimately fatal prognosis; 40% were nursed in intensive care units. Clinical response among patients with pneumonia (73% in the ceftazidime group vs. 65% in the ceftriaxone/tobramycin group), septicemia (73% vs. 59%), and complicated urinary tract infections (80% vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 16 publications
1
33
1
6
Order By: Relevance
“…Similarly, in a prospective study of 189 consecutive episodes of P. aeruginosa bacteremia, the investigators found that survival was no greater in patients who received two or more antibiotics with in vitro activity against P. aeruginosa (therapies not specified) than in patients who received a single agent with in vitro activity (246). A prospective, randomized clinical trial comparing ceftazidime monotherapy with ceftriaxone and tobramycin for serious infections with Gram-negative bacteria, including Pseudomonas spp., showed similar mortality between the groups (211). The authors' definition of combination therapy was essentially aminoglycoside monotherapy for Pseudomonas spp.…”
Section: Pseudomonas Aeruginosa Infectionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, in a prospective study of 189 consecutive episodes of P. aeruginosa bacteremia, the investigators found that survival was no greater in patients who received two or more antibiotics with in vitro activity against P. aeruginosa (therapies not specified) than in patients who received a single agent with in vitro activity (246). A prospective, randomized clinical trial comparing ceftazidime monotherapy with ceftriaxone and tobramycin for serious infections with Gram-negative bacteria, including Pseudomonas spp., showed similar mortality between the groups (211). The authors' definition of combination therapy was essentially aminoglycoside monotherapy for Pseudomonas spp.…”
Section: Pseudomonas Aeruginosa Infectionsmentioning
confidence: 87%
“…The ability of this organism to simultaneously express multiple mechanisms of resistance adds to the challenge of effectively treating it (104,157). Several studies evaluating morbidity and mortality with dual and single antipseudomonal agents for the treatment of P. aeruginosa infections have been conducted, as outlined below (7,15,44,70,112,152,180,211,224,227,228,246).…”
Section: Pseudomonas Aeruginosa Infectionsmentioning
confidence: 99%
“…The debate is still in place, since clinical studies were not able to demonstrate the superiority of synergistic effect on clinical outcomes. [21][22][23] Other potential disadvantages of combination therapy mainly consist of increasing toxicity, costs and possible emergence of multiple resistance and risk of bacterial and fungal superinfections. 24 Current guidelines suggest empirical combination therapy with two or more antibacterial agents for neutropenic patients, for those at risk of multiple drugs resistant pathogens and for those with severe pneumonia and septic shock.…”
Section: What Does Appropriate Antimicrobial Therapy Mean and How To mentioning
confidence: 99%
“…It was concluded that combination therapy using a fourth-generation cephalosporin with either an aminoglycoside or a fluoroquinolone was not associated with a clinical or biological benefit when compared with cephalosporin monotherapy for common, susceptible pathogens causing VAP [5]. Of the many comparative studies for the treatment of VAP, six are summarised in table 2 [6][7][8][9][10][11]. Perhaps the best of these studies compared imipenem alone with the combination of imipenem and netilmicin [8].…”
Section: Monotherapy Versus Combination Therapy: Comparisons Of Efficacymentioning
confidence: 99%